THE INFLUENCE OF THE MEANS OF GENERAL PHYSICAL TRAINING ON THE BIOMECHANICAL INDICATORS OF PERFORMING A HIT WITH A CLUB BY YOUNG GOLFERS - Cherkashina E.V. ,; Ning Ji,; Baishev A.A. ,; Bessonova V.P. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop a methodology for the general physical training of golfers at the initial stage and evaluate its effectiveness in the course of a pedagogical experiment. Methods and structure of the study. The pedagogical experiment involved 60 golfing boys, whose age was 9.00±0.82 years. In the experimental (EG) and control (CG) groups of 30 people each. During the four-month mesocycle, the developed methodology of physical training was introduced into the training process of the EG. Representatives of the CG trained according to a different methodology, which consisted only of playing golf in the field or using golf simulators. Twice (before and after a four-month training mesocycle) in both groups, pedagogical testing was carried out, indicators of carpal dynamometry, proprioceptive sensitivity, biomechanical indicators of the performance of a blow with a club using a Ruge indoor golf simulator were determined. The studies were carried out on the basis of the golf club in Shenzhen, China. Results and conclusion. The effectiveness of the developed method of general physical training of 8-10 year old boys involved in golf was assessed in the process of a pedagogical experiment. The analysis of intergroup differences in the results of pedagogical testing showed that in the EG at a statistically significant level relative to the initial data, in comparison with the representatives of the CG, 14 parameters out of 15 studied significantly increased (p<0.01). Growth rates, expressed as a percentage, ranged from 4% to 48.9% (p<0.01). Also, in the representatives of the EG relative to the athletes of the CG, five indicators of the biomechanical analysis of the club stroke performed with the use of a golf simulator changed at a significantly significant level: the distance that the ball flew and rolled on the ground (yard), the distance of the ball flight (yard), the angle of the ball departure and club shaft angle (0), club head speed (miles·hour-1) (p < 0.01).